If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x * ln(3) = 2 + -1x * ln(2) Reorder the terms for easier multiplication: 3x * ln = 2 + -1x * ln(2) Multiply x * ln 3lnx = 2 + -1x * ln(2) Reorder the terms for easier multiplication: 3lnx = 2 + -1 * 2x * ln Multiply -1 * 2 3lnx = 2 + -2x * ln Multiply x * ln 3lnx = 2 + -2lnx Solving 3lnx = 2 + -2lnx Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add '2lnx' to each side of the equation. 3lnx + 2lnx = 2 + -2lnx + 2lnx Combine like terms: 3lnx + 2lnx = 5lnx 5lnx = 2 + -2lnx + 2lnx Combine like terms: -2lnx + 2lnx = 0 5lnx = 2 + 0 5lnx = 2 Divide each side by '5nx'. l = 0.4n-1x-1 Simplifying l = 0.4n-1x-1
| 0.02x-1.56=0.8x | | x-34=72 | | 14=.6(9y-15) | | 10c=260 | | 3(2a-6)=34 | | 9h=207 | | 34(19-5.5x)=16(5x-8)+53.1 | | 7g=91 | | 32=.5x(x+12) | | 7p=56 | | -1+-10= | | -3.45-1.5c=6.1(c+2.3) | | 0.3a-1.2=0.5a | | 36=.5x(x-5) | | f+20=61 | | 14a-10=19(a-3) | | 2.8x+65=5.3x+10 | | 8x+5y = 6 | | 3n-8=37+8n | | 7x-7=3x+9 | | e+49=61 | | 26-2(5+6)= | | x-6+2=4 | | 1.7m+7.28=-9.04 | | 8z-5=-11+5z | | d+13=35 | | e-27=19 | | 2x^2-40x=0 | | b+14=33 | | 4y^2+31y-8=0 | | d-41=34 | | 14(x-2)-4=12x+2 |